The Effect of Customer Perceived Value on Purchase Intention of Body Shop Through Purchase Experience and Product Attitude - William Satyaputra Adam; Christian Suhartono (iBuss Management, 2021)
With the increasing of plastic waste pollution year by year globally, the British cosmetics Body Shop has taken action to reduce plastic waste pollution. One of the actions is recycling plastic products into something useful (plastic bottle packaging). Thus, this research objective is to analyse the influence of green value, functional value, emotional value, aesthetic value, social value, self-expression value towards recycled product attitude. Also, to identify the influence of mediation between perceived values and purchase intention and whether purchase experience gives moderation impact between perceived values and purchase intention of recycled product. We use 90 respondents for our research, and this research will collect data using a non-probablility sampling method distributed through an online platform. To analyse the data, this research will use Path Analysis to evaluate the relationship of the proposed framework. In conclusion,  out of those six values that we have mentioned, the significant ones are green, emotional, and aesthetic value. As for functional value, social value and self-expression value are insignificant towards recycled product attitude. The influence of mediation between perceived values and purchase intention is significant. However, whether purchase experience gives moderation impact between perceived values and purchase intention of recycled products is insignificant.Keywords:Customer Perceived Value, Purchase Intention, Body Shop, Purchase Experience, Product Attitude.